Cara Pandang Gereja terhadap Kemiskinan dan Pembangunan - Viktorahadi, Bhanu; Haq, Mochamad Ziaul; Huriani, Yeni (Hanifiya: Jurnal Studi Agama-Agama, 2021)
Poverty is a social reality in the dynamics of human life in the world. This social reality is also part of the Church's concern. The Church pays attention, cares, and conveys its teachings about poverty and ways to overcome it through its dynamic structure, which includes Scripture, Tradition, and the Magisterium. This study is literature research, with Indonesian contextualization. By textual analysis, this paper shows that in reflecting on various realities related to poverty, especially by using the scalpel of Theology of Liberation, the Church has concluded that poverty, especially structural poverty, is the fruit of social sin. Social sin is an individual sin built in such a way with various kinds of conditioning to become a massive structure. This study recommends the need for personal and communal repentance to destroy this structure of sin and, at the same time, lift people out of structural poverty.